THE EXPERIENCE OF ADALIMUMAB USE IN A PATIENT WITH PAUTSIARTICULAR JUVENILE ARTHRITIS AND UVEITIS - E.I. Alexeeva; E.V. Mitenko; T.M. Bzarova; S.I. Valieva; A.M. Chomakhidze; K.B. Isaeva; E.G. Chistyakova; R.V. Denisova; T.V. Sleptsova; T.Yu. Polyaeva; A.N. Fetisova (Union of pediatricians of Russia, 2011)
The article presents the observation of early debut and the severe course of the juvenile polyarthritis involving the eyes, refractory to treatment by classical immunosuppressants. Successful use of the genetically engineered biological drug - adalimumab is described:  by the 4th week of therapy the acute inflammatory changes in affected joints were stopped, range of motion in them fully recovered; to the 8th week uveitis remission was registered, laboratory values of the disease activity were normalized: erythrocyte sedimentation rate, serum concentration of C-reactive protein. Key words: children, juvenile rheumatoid arthritis, rheumatoid uveitis, adalimumab. (Pediatric pharmacology. - 2011; 8 (6): 119-124).